Highly sensitive DNA sensor based on upconversion nanoparticles and graphene oxide - Alonso-Cristobal, P; Vilela, P; El-Sagheer, A; Lopez-Cabarcos, E; Brown, T; Muskens, O; Rubio-Retama, J; Kanaras, A (American Chemical Society, 2015)
In this work we demonstrate a DNA biosensor based on fluorescence resonance energy transfer (FRET) between NaYF4:Yb,Er nanoparticles and graphene oxide (GO). Monodisperse NaYF4:Yb,Er nanoparticles with a mean diameter of 29.1 ± 2.2 nm were synthesized and coated with a SiO2 shell of 11 nm, which allowed the attachment of single strands of DNA. When these DNA-functionalized NaYF4:Yb,Er@SiO2 nanoparticles were in the proximity of the GO surface, the π-π stacking interaction between the nucleobases of the DNA and the sp(2) carbons of the GO induced a FRET fluorescence quenching due to the overlap of the fluorescence emission of the NaYF4:Yb,Er@SiO2 and the absorption spectrum of GO. By contrast, in the presence of the complementary DNA strands, the hybridization leads to double-stranded DNA that does not interact with the GO surface, and thus the NaYF4:Yb,Er@SiO2 nanoparticles remain unquenched and fluorescent. The high sensitivity and specificity of this sensor introduces a new method for the detection of DNA with a detection limit of 5 pM.